Influence of different small-sided games on physical and physiological demands in rugby union players - Teixeira Vaz, L. M.; Varanda Goncalves, B. S.; Nogueira Figueira, B. E.; Garcia, G. C. (International Journal of Sports Science & Coaching, 2016)
This study aimed to describe the influence of four different small-sided games with 15-min duration on physical and physiological demands in rugby union players. Fourteen rugby union players (22.4±3.2 years) participated in the study that was conducted during the competitive period of final-four first Division of 2012-2013 qualifying competition. Time-motion and body impact data were collected using global positional systems technology with heart rate monitored continuously across training sessions. The present study found that interaction between speed zones, impacts zones and small-sided game formats was significant. No differences were found in the distance covered per minute or the interaction of heart rate values; however, players spent the majority of time above 90% of the HRmax. The SSG 1 presents significant lower values in body impacts per minute compared with the other small-sided games. The results of this study demonstrate that small-sided games with evasion skills showed different levels of physical performance, and skill qualities of rugby union players. Although HR responses were similar between all small-sided game formats, the high levels of individual variability may explain the obtained results. Future use of this technology may help practitioners in design and implementation of individual position-specific training programs with appropriate management of player exercise load.